2019
DOI: 10.1038/s41598-019-39571-x
|View full text |Cite
|
Sign up to set email alerts
|

Definition of a cell surface signature for human cardiac progenitor cells after comprehensive comparative transcriptomic and proteomic characterization

Abstract: Adult cardiac progenitor/stem cells (CPC/CSC) are multipotent resident populations involved in cardiac homeostasis and heart repair. Assisted by complementary RNAseq analysis, we defined the fraction of the CPC proteome associable with specific functions by comparison with human bone marrow mesenchymal stem cells (MSC), the reference population for cell therapy, and human dermal fibroblasts (HDF), as a distant reference. Label-free proteomic analysis identified 526 proteins expressed differentially in CPC. iTR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
53
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(59 citation statements)
references
References 55 publications
6
53
0
Order By: Relevance
“…Based on complementary previous analyses, both with CPC [29] and pCPC (Prat et al 2019, in preparation), an important global similarity between porcine-derived CPC and human-derived CPC was established. We then validated some of the array-based findings analyzing by RT-qPCR expression of F11R (F11 receptor) and CACNG7 (calcium channel, voltage-dependent, gamma subunit 7), both proposed as CPC markers [29]. Both genes demonstrated a similar expression profile, by RT-qPCR, in pCPC and CPC (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Based on complementary previous analyses, both with CPC [29] and pCPC (Prat et al 2019, in preparation), an important global similarity between porcine-derived CPC and human-derived CPC was established. We then validated some of the array-based findings analyzing by RT-qPCR expression of F11R (F11 receptor) and CACNG7 (calcium channel, voltage-dependent, gamma subunit 7), both proposed as CPC markers [29]. Both genes demonstrated a similar expression profile, by RT-qPCR, in pCPC and CPC (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Zhou et al (2017) also demonstrated that the marker SIX2 is able to target temporally distinct cell subpopulations from second heart field-associated CPCs [189]. One very recent study (Torán et al, 2019) used proteomic and genomic approaches to comprehensively characterize the proteome of human adult c-KIT CPCs [190]. It was demonstrated that these CPCs highly express 4 surface markers: GPR4 (G protein-coupled receptor 4), CACNG7 (calcium voltage-gated channel auxiliary subunit gamma 7), CDH5 (VE-cadherin) and F11R (F11 receptor) in comparison to mesenchymal stem cells, human dermal fibroblasts and cardiac fibroblasts.…”
Section: Isolation Of Cpcsmentioning
confidence: 99%
“…Thus, new markers are continuously being discovered to isolate specific CPC populations. However, they are frequently identified in CPCs derived from neonatal/adult tissue but fewer in ESC-CPCs and iPSC-CPCs [107,133,134,[190][191][192]. Further validation of such markers is vital to assign a common signature that accurately identifies these cells.…”
Section: Isolation Of Cpcsmentioning
confidence: 99%
“…Many subtypes of cardiac stem cells have been reported (Chong et al, 2014), and apparently, the paracrine factors released are also diversified between them; however, the therapeutic effects occur with the different CPC populations. Recently, Torán et al (2019) aimed to define a set of proteins specifically secreted by CPC. Authors isolated human CPC from myocardial samples and conducted a proteomic assay.…”
Section: Cardiac Soluble Factors: Effects On Cardiomyocyte Fate and Bmentioning
confidence: 99%
“…Authors isolated human CPC from myocardial samples and conducted a proteomic assay. The analysis identified a group of factors expressed at high to medium levels by CPC that included IL-1, GROa (CXCL1), CXCL6 (GCP2), and IL-8 (Torán et al, 2019). Similarly, considering the effects of CPC in myocardial recovery, Sharma et al (2017) isolated cardiac progenitor cells from neonatal (nCPC) and adult patients (aCPC) and compared the functionality of their conditioned medium.…”
Section: Cardiac Soluble Factors: Effects On Cardiomyocyte Fate and Bmentioning
confidence: 99%